2007
DOI: 10.1111/j.1460-9568.2006.05245.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase‐3 inhibition is integral to long‐term potentiation

Abstract: Glycogen synthase kinase-3 (GSK-3) is a serine/threonine kinase regulating diverse cellular functions including metabolism, transcription and cell survival. Numerous intracellular signalling pathways converge on GSK-3 and regulate its activity via inhibitory serine-phosphorylation. Recently, GSK-3 has been involved in learning and memory and in neurodegeneration. Here, we present evidence that implicates GSK-3 in synaptic plasticity. We show that phosphorylation at the inhibitory Ser9 site on GSK-3beta is incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
252
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 308 publications
(270 citation statements)
references
References 38 publications
15
252
3
Order By: Relevance
“…6 A). To further confirm the changes of these postsynaptic proteins, we prepared the P2 fraction to enrich the synaptic associated proteins (Hooper et al, 2007). We found that the levels of NR2A/B subunits were also reduced in addition to a more prominent decrease of PSD93 after wortmannin treatment, and these proteins were partially restored when GSK-3 was si- Figure 3.…”
Section: Upregulation Of Gsk-3 Reduces the Level Of Psd93 And Nr2a/bmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A). To further confirm the changes of these postsynaptic proteins, we prepared the P2 fraction to enrich the synaptic associated proteins (Hooper et al, 2007). We found that the levels of NR2A/B subunits were also reduced in addition to a more prominent decrease of PSD93 after wortmannin treatment, and these proteins were partially restored when GSK-3 was si- Figure 3.…”
Section: Upregulation Of Gsk-3 Reduces the Level Of Psd93 And Nr2a/bmentioning
confidence: 99%
“…A most recent study demonstrated that GSK-3 was inhibited during LTP, and it was activated during long-term depression (Peineau et al, 2007). Another recent study showed that conditional expression of GSK-3 in mouse brain inhibited LTP (Hooper et al, 2007). Until now, the possible molecular link between GSK-3 and LTP is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of GSK-3b during LTP has been hypothesized to prevent early subsequent LTD (Peineau et al 2007). Accordingly, LTP induction is associated with inhibition of GSK-3b (Hooper et al 2007). Inhibitory S9 phosphorylation of GSK-3b increases in hippocampus and amygdala during fear LTM formation (Fujio et al 2007;Maguschak et al 2008).…”
Section: Pi3kmentioning
confidence: 99%
“…Furthermore, in the FTDP-17 model animal, Li + , which inhibits GSK-3β, prevented NFT formation (16,37). Overexpression of GSK-3β in mouse induces tau hyperphosphorylation and a decline in cognitive performance accompanied with inhibition of LTP (20,33). This decline in cognitive performance is due to impairment of learning.…”
Section: Activation Of Gsk-3β During Aging Brainmentioning
confidence: 99%
“…Activation of GSK-3β is required for LTD but inhibits LTP (33). The inhibition of LTP by activation of GSK-3β impaired learning ability.…”
Section: Regulation Of Synaptic Function By Gsk-3βmentioning
confidence: 99%